THE RELATIONSHIP BETWEEN PRODUCT QUALITY AND RETURN SERVICE WITH SHOPEE CUSTOMER SATISFACTION - Nurbaiti, Nurbaiti; Pratama, Reza Hardian (Jurnal Manajemen, 2024)
This study aims to examine the relationship between product quality, return services, and customer satisfaction on Shopee, one of the leading e-commerce platforms in Southeast Asia. The rapid growth of e-commerce has drawn greater attention to customer satisfaction, which is influenced by various factors such as product quality and the efficiency of return services. Using purposive sampling with a sample of 200 respondents, and employing Smart PLS for data analysis, this research analyzes Shopee users' perceptions regarding the quality of the products they purchase and their experience with the return process on the platform. Data were collected from a sample of Shopee customers, and statistical methods such as correlation analysis and regression were used to assess the impact of product quality and return services on customer satisfaction. The results indicate that both product quality and return services have a significant positive effect on customer satisfaction. Specifically, products that meet customer expectations and a smooth, hassle-free return process contribute to higher satisfaction levels, which in turn enhance customer loyalty and the likelihood of repeat purchases. These findings provide valuable insights for Shopee to continue improving its services and maintain a competitive edge in the e-commerce market.